2023
DOI: 10.1093/jac/dkad358
|View full text |Cite
|
Sign up to set email alerts
|

Variation in antibiotic consumption in very preterm infants—a 10 year population-based study

Zuzana Huncikova,
Hans Jørgen Stensvold,
Knut Asbjørn Alexander Øymar
et al.

Abstract: Objectives Wide variations in antibiotic use in very preterm infants have been reported across centres despite similar rates of infection. We describe 10 year trends in use of antibiotics and regional variations among very preterm infants in Norway. Patients and Methods All live-born very preterm infants (<32 weeks gestation) admitted to any neonatal unit in Norway during 2009–18 were included. Main outcomes were antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…The overall rate of VLBW infants exposed to antibiotics at any time during hospital stay is slightly lower in our centre (75% vs. 80%) than the one reported in a recent Norwegian nationwide study, although our overall antibiotic use during the hospital stay is higher (DOT/1000 PD 267 vs. 149) [14]. Among 5296 infants (with a comparable gestational age and birth weight), Norwegian investigators reported a reduction in DOT/1000 PD over 10 years [14]. Although the reasons for these discrepancies are unclear, repeated courses of antibiotics or prolonged therapies in cases of culture-positive sepsis would explain our results.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…The overall rate of VLBW infants exposed to antibiotics at any time during hospital stay is slightly lower in our centre (75% vs. 80%) than the one reported in a recent Norwegian nationwide study, although our overall antibiotic use during the hospital stay is higher (DOT/1000 PD 267 vs. 149) [14]. Among 5296 infants (with a comparable gestational age and birth weight), Norwegian investigators reported a reduction in DOT/1000 PD over 10 years [14]. Although the reasons for these discrepancies are unclear, repeated courses of antibiotics or prolonged therapies in cases of culture-positive sepsis would explain our results.…”
Section: Discussioncontrasting
confidence: 76%
“…Wide variations exist in empirical antibiotic use in NICUs despite comparable infection rates and antibiotic resistance profiles [ 13 , 14 , 15 , 16 ]. There are many reasons for this, including limited pharmacokinetic and pharmacodynamic data in preterm and term infants and few high-quality clinical trials on which expert consensus or international guidelines for treatment and prophylaxis can rely [ 14 , 15 ]. However, comparing one’s NICU with population-based studies from different regions and centres may lead to revisiting one’s work and reconsidering one’s approaches [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations